SYSTEM OF SOCIAL SERVICES IN THE CONTEXT OF POSSIBLE CHANGES DUE TO THE INFLUENCE OF ENTREPRENEURSHIP ACTIVITIES - Lukáš Stárek; Aleš Zpěvák (Fonseca, Journal of Communication, 2024)
In Europe and also in Czechia, we can observe the recent trend of social services maintained by entrepreneurship companies. Mainly, it involved private companies focused on providing social services. Even though the number of social services has grown, the capacity that is provided is not sufficient, and there is still a lack of these services. This is caused due to the changes occurring in social services. In the majority of European countries, there is a growing trend of privatizing and marketizing these services – mainly within the providers of residential services and long-term services. That directly leads towards the growth of the number of private providers while the number of public providers is lowering. On the other hand, private providers can be found in other spheres of the market. The aims of this article are to shed light on primary institutions, whose understanding is crucial in their realizations, and to critically evaluate this recent society’s status.